ANALISIS PERATAAN LABA DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Widaryanti . (STIE Pelita Nusantara Semarang, 2009)
The objective of this research is to examine factors that influencing income smoothing practice in manufacturing companies listed at Indonesian Stock Exchange (IDX). The factors being examined were size, profitability, financial leverage, net profit margin and variance of stock value. Eckel’s Index (1981) was used to determine the incidence of income smoothingpractice with net profit after tax as the object of income smoothing.The sample of this research selected by purposive judgement sampling. The samples were 49 manufacturing companies listed at IDX for five years period (2002-2006). Multivariate test (logistic regression) were used to identify the factors affecting the income smoothing practice.The result of Eckel’s Index (1981) showed that income smoothing is practiced bymanufacturing companies listed at IDX. The multivariate test showed that size, profitability, financial leverage, net profit margin and variance of stock value, simultaneously and partial test not having a significance influence on income smoothing practice. In conclusion, from five independen variables being examined, there are’nt affecting the income smoothing practice.